2000
DOI: 10.1002/(sici)1521-3773(20000204)39:3<629::aid-anie629>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Phosphonolipids Containing Quaternary Phosphonium and Arsonium Groups for DNA Transfection with Good Efficiency and Low Cellular Toxicity**

Abstract: Replacing the ammonium polar head in cationic lipids 1 (A=N) by a phosphonium or an arsonium group (A=P, As) improves their properties as synthetic vectors for DNA transfection. The increased volume of the cationic head is supposed to modify the interactions of the vector with the solvent and DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 13 publications
3
46
0
Order By: Relevance
“…For example, Floch and coworkers demonstrated that use of phosphorus or arsenic atoms instead of nitrogen, which incorporate phosphonate linkers, convey cationic charge and result in improved transfection efficiency and reduced cytotoxicity. 13 …”
Section: Vector Design and Formulationmentioning
confidence: 99%
“…For example, Floch and coworkers demonstrated that use of phosphorus or arsenic atoms instead of nitrogen, which incorporate phosphonate linkers, convey cationic charge and result in improved transfection efficiency and reduced cytotoxicity. 13 …”
Section: Vector Design and Formulationmentioning
confidence: 99%
“…Due to the negatively charged surface of bacterial membrane, it is reasoned that the strong polarization effect of phosphorus facilitates QPS to adsorb bacteria. Apart from the enhanced antibacterial activity, QPS‐containing macromolecules possess improved thermal and pH stability as well as higher conductivity as compared with ammonium analogs because of the weaker electronegativity of phosphorus . Furthermore, many researchers have revealed the high flame retardancy of phosphorus‐containing compounds .…”
Section: Introductionmentioning
confidence: 99%
“…Later, many studies have proven that DOTAP is a feasible and efficient cationic lipid in gene delivery [ 162 , 163 , 164 , 165 ]. Other cationic lipids apart from quaternary ammonium lipids have also been developed through the delocalization of cationic head groups, such as guanidinium lipids, imidazolium lipids, pyridinium lipids, piperidinium lipids, pyrrolidinium lipids, and phosphonium lipids [ 166 , 167 , 168 , 169 , 170 , 171 , 172 ].…”
Section: Modifications Of Lipid-based Nanoparticlesmentioning
confidence: 99%